Assessment of damage due to aila of post SIDR agricultural rehabilitation: insights from sharankhola, Bagerhat - Hossain, S. M. Alamgir (BRAC University, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2009.